Professor Vira V. Protopopova: the 75 Anniversary - Latowski, Karol; Celka, Zbigniew; Mosyakin, Sergei L.; Shevera, Myroslav V.; Ilyinska, Antonina P.; Tymchenko, Iryna A. (Biodiversity: Research and Conservation, 2008)
Professor Vira V. Protopopova celebrates her 75th anniversary. She is well known in Ukraine and far beyond as a famous Ukrainian botanist who made a great contribution to botanical science, especially to studies of plants invasions, alien species, taxonomy of orchids (Orchidaceae), composites (Asteraceae), ferns (Polypodiophyta) and fern allies (Lycopodiophyta and Equisetophyta) and many other families of plants. Professor V. Protopopova is also a recipient of the M. G. Kholodny Award of the National Academy of Sciences of Ukraine, Honorary Member of the Ukrainian Botanical Society and Head Researcher at the M. G. Kholodny Institute of Botany, National Academy of Sciences of Ukraine.